A primer for poets & readers of poetry - Orr, Gregory (W. W. Norton & Company, 2018)
"Guides the young poet toward a deeper understanding of how poetry can function in his or her life, while introducing the art in an exciting new way...It provides the poet with more than a dozen focused writing exercises and explains essential topics such as the personal and cultural threshold; the four corces that animate poetic language (naming, singing, saying, imagining); tactics of revision; ecstasy and engagement as motives for poetry; and how to locate and learn from our personal poetic forbears."--Back cover.